The Effect of Place on the Textual Structure of the Epic of Gilgamesh - Israa Faraj Lafta Al-Rubaie (Zanco Journal of Human Sciences, 2025)
The place constitutes a visual concept that is furnished to indicate according to tangible possibilities and deepens the meaning according to a tangible cultural memory, which frames the epic literary event with dimensions with scenes that parallel the movement of time and act as an alternative to it within the artistic structure. The geography of the place in epic literature is considered a symbolic surplus that allows the production and formation of human cultural memory even It is able to give a symbolism derived from the topography of the place in which the event moves. The literary place has two dimensions that can be monitored through the framework of possible reality. The first includes the description that usually dominates the literary work in order to formulate a theater that moves according to the dimensions of the events. The second dimension is the expected dimension. Which takes the capabilities of language and imagination as a way to monitor and follow up. Man has realized from time immemorial the necessity of his need for place in his life, and this realization stemmed from his stability and permanence. Thus, the focus was one of the important textual strategies that modern writings resort to. Place in the narrative text depends on the framework in which it is located. In it, the events and transitions that take place between multiple places are followed by a complete transformation in the character’s ideology, and the significance of the place has a great impact on the psyche of the person who lives in it. The openness, expansion, and development leave a positive stamp on the individual’s reality, and the place is considered one of the most important effective narrative elements that are employed within the mythical narrative structure because it It represents the space in which the events of the Epic of Gilgamesh take place. It has its own significance, whether realistic or mythical, inspired by imagination. In all cases, the place contributes to the structure of the narrative text of the epic, and this is what the ancient Iraqi writer realized. Either the legendary place has a specificity that surpasses other places, and we find Most myths open with a description or mention of a specific place. The legendary place is often linked to the gods, so it has existed since time immemorial. They considered the first legendary place to come into existence, and other places branched out from it. The relationship of the epic or legend to the place is the relationship of the artistic structure to its symbols, that is, the real places in this world. It does not exist in myth, and from this standpoint we will highlight the importance of place and its impact on the construction of the epic text, which is the title of our research (The impact of place on the textual construction of the Epic of Gilgamesh Based on the requirements of the research idea and the available scientific material, the research was divided into two axes: the concept of place and its significance, and the second axis is the importance of the geography of the place in constructing the literary narrative text. The research was preceded by an introduction and the most prominent conclusions that we reached when writing.